Implementation and sustainability of a medication reconciliation toolkit: A mixed methods evaluation. - Stolldorf, Deonni P; Mixon, Amanda S; Auerbach, Andrew D; Aylor, Amy R; Shabbir, Hasan; Schnipper, Jeff; Kripalani, Sunil (American Journal of Health-System Pharmacy, 2020)
Purpose MARQUIS (Multi-Center Medication Reconciliation Quality Improvement Study) provided participating hospitals with a toolkit to assist in developing robust medication reconciliation programs. Here we describe hospitals' implementation of the MARQUIS toolkit, barriers and facilitators, and important factors that may enhance the spread and sustainability of the toolkit. Methods We used a mixed methods, quantitative-qualitative study design. We invited site leaders of the 5 hospitals that participated in MARQUIS to complete a Web-based survey and phone interview. The Consolidated Framework for Implementation Research guided question development. We analyzed the collected data using descriptive statistics (for survey responses) and thematic content analysis (for interview results). Results Site leaders from each MARQUIS hospital participated. They reported that MARQUIS toolkit implementation augmented their hospitals' existing but limited medication reconciliation practices. Survey results indicated executive leadership support for toolkit implementation but limited institutional support for hiring staff (reported by 20% of respondents) and/or budgetary support for implementation (reported by 60% of respondents). Most participating hospitals (80%) shifted staff responsibilities to support medication reconciliation. Interview findings showed that inner setting (ie, organizational setting) and process factors (eg, designation of champions) both inhibited and facilitated implementation. Hospitals adopted a variety of toolkit interventions (eg, discharge medication counseling) using a range of implementation strategies, including development of educational tools and tip sheets for staff members and electronic health record templates. Conclusion Despite limited institutional support, hospitals can successfully implement, spread, and sustain the MARQUIS toolkit by shifting staff responsibilities, adding pharmacy staff, and using a variety of strategies to facilitate implementation. Although leadership support and resources for data collection and dissemination facilitated implementation, limited staff buy-in and competing priorities may hinder implementation.